حرف العطف بين اللغتين العربية والإندونيسية (دراسة تحليلية تقابلية في كتاب القواعد الأساسية للغة العربية وكتاب Bahasa Indonesia Ilmiah) - Zainab Zainab (IAIN MADURA, 2018)
The book of Qawaid Asasiyat lilughatil 'Arabiyat is written by Ahmad al-Hasyimi bik bin Ibrahim bin Mustafa bin Muhammad Nafi'. This book contains the principles of Arabic such as the use of Arabic conjunctions. Meanwhile, the book of Bahasa Indonesia Ilmiah contains the principles of Indonesian which also explains about conjunctions. This research is aimed to know what types of conjunctions found in Qawaid Asasiyat Lilughatil ‘Arabiyat book? The second focus is what types of conjunctions found in the book of Bahasa Indonesia Ilmiah? The third focus is how are the similarities and the differences between conjunctions in Qawaid Asasiyat lilughatil ‘Arabiyat and in the book of Bahasa Indonesia Ilmiah. The data sources in this research were Qawaid Asasiyat lilughatil ‘Arabiyat book, Nahwul Wadafi. Data collection procedures used was documentation, while the method utilized in this research was qualitative and contrastive content analysis. The results revealed that in the book of Qawaid Asasiyat lilughatil ‘Arabiyat, there are nine types of conjunctions; wawu, fa’, tsumma, hatta, aw, bal, laa, and lakinna. While, in the book of Bahasa Indonesia Ilmiah used four types of conjunctions, those are coordinating conjunctions, correlative conjunctions, subordinating conjunctions, and conjunctions that relate one sentence to another.